2015
DOI: 10.3832/ifor1203-007
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of regional climate change on site productivity of Larix olgensis plantations in northeast China

Abstract: © iForest -Biogeosciences and Forestry IntroductionUnderstanding how climate change affects forest site productivity is of great importance for adaptive forest management under climate change conditions. Forest site productivity, as a quantitative estimate of the potential for producing plant biomass at a site, is a significant indicator of forest quality, as well as an important variable of forest growth models in forest management (Skovsgaard & Vanclay 2008). However, site productivity presents great spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
1
12
1
Order By: Relevance
“…Although temperature is also a key factor in forest growth [48,49], the correlation between temperature and forest growth was inconsistent in previous studies, even for larch in China. Shen et al [30] found an opposite result to the present study, i.e., that temperature showed a negative effect on site index of Larix olgensis in Jilin, China. However, Zhang et al [49] found a significantly positive correlation between temperature and tree-ring width for Dahurian larch in Inner Mongolia, northeastern China.…”
Section: Climate-sensitive Dominant Height Growth Modelcontrasting
confidence: 99%
See 3 more Smart Citations
“…Although temperature is also a key factor in forest growth [48,49], the correlation between temperature and forest growth was inconsistent in previous studies, even for larch in China. Shen et al [30] found an opposite result to the present study, i.e., that temperature showed a negative effect on site index of Larix olgensis in Jilin, China. However, Zhang et al [49] found a significantly positive correlation between temperature and tree-ring width for Dahurian larch in Inner Mongolia, northeastern China.…”
Section: Climate-sensitive Dominant Height Growth Modelcontrasting
confidence: 99%
“…PWM showed a positive effect on the maximum dominant height, and TWQ showed a positive effect on the rate of dominant height growth. Many studies have found that precipitation is a key factor that has often been shown to have positive effects on the growth of larch plantations [30,47]. For example, the positive effects of precipitation on stand dominant height growth were also found for jack pine and black spruce [24], and these findings are consistent with those of the present study.…”
Section: Climate-sensitive Dominant Height Growth Modelsupporting
confidence: 92%
See 2 more Smart Citations
“…Zhao et al (2009Zhao et al ( , 2011 predicted that the NPP of coniferous and broad-leaf mixed forests in northeastern China had an increasing trend under future climate warming, using the GLOPEM-CEVSA model. Shen et al (2015) studied the potential impacts of regional climate change on productivity of Larix olgensis in northeastern China using a generalized additive model (GAM) and found that the change of mean site productivity of Larix olgensis would vary from 2.2 to -5.9% by 2050 and from 3.7 to -11.8% by 2070 under three BC-RCP scenarios with rising temperature and increasing precipitation. Although all RCPs scenario simulations indicated that forest PP would increase by the end of this century in response to future climate changes, the magnitude of this increase varies markedly among different areas (PP increased by 8.19-15.30% in SE, 1.38-9.36% in CB, 3.48-11.56% in SW from the present to 2070).…”
Section: Forest Potential Productivity Under Future Climate Change Scmentioning
confidence: 99%